A concise synthesis of indolo[2, 1-a]isoquinoline via alkyne annulations promoted by base. (5th January 2022) - Mehmood, Hina; Iqbal, Muhammad Asif; Hua, Ruimao
Graphical abstract: Abstract: A convenient and one-pot synthetic method for the construction of indolo[2, 1- a ]isoquinolines is developed by the dehydrative cyclocondensation reactions of the easily available 2-hydroxymethyl anilines with 2-ethynylbenzaldehydes in DMSO in the presence of KOH and TBAI under air.